Structural-contental definiteness of actualization of athletes' thinking types in the context of the system-activity approach - Kim, T. K.; Pleshakov, A. A.; Kuzmenko, G. A.; Ivankov, Ch. T. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to substantiate the conjugation of the types of thinking in the context of the structural-content components of the athlete's activity in the implementation of intellectual tasks in the process of learning motor actions.